Moderasi Beragama Berbasis Komunitas (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
Religious moderation with unconditional acceptance is the ideal of all humans in this world, therefore the most basic DNA imprint in humans is peace. Therefore, humans must hate violence in any name. Humans must respect, accept, respect and uphold human values. The idea of the religious moderation movement cannot be separated from the long road to militating the social system which has led to the destruction of the social system. The news presented on television and on social media homepages about corruption, collusion and nepotism, rape, theft, robbery, drug abuse, social violence and domestic violence, bullying and conflicts in society because of differences inter and interreligious. This paper assumes that all social problems involving individuals, groups and organizations in society stem from abnormal encounters. Because every time humans cannot avoid an encounter and use language, the improvement begins in that realm. Considering that improving the social system to create religious moderation should not be elitist and costly, the approach must be with a populist approach. Sekolah Perjumpaan is a simple technology but very principal, namely how to optimize encounters and prioritize action.
Keywords: Religious Moderation; Community; Sekolah Perjumpaan; Language Action